Factors Influencing Students' Perception on Information Security Plan in UUM - Adebola, Babatunde Dorcas (2010)
This thesis seeks to determine the factors influencing information security plan in Universiti Utara Malaysia (UUM). Although, there are various means by which higher institutions of learning in Malaysia have implemented technical solutions to protect information from various ways in order to prevent internal security breaches. Therefore, an approach which would be emphasized and determine information security plan within higher institutions is much needed to make an impact on the day to day security task of the employees.